Pengaruh Perbedaan Asas-Asas Hukum Pidana Umum dan Hukum Militer Terhadap Hak Asasi Manusia Dalam Sistem Hukum Nasional - Karina Hasiyanni Manurung; Rangga Wira Syahputra; Reza Ferdiansyah; Shavina Putri Ferdianty; Irwan Triadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Indonesian law consists of two separate legal frameworks such as general criminal law and military law. General criminal law applies to civilians and is based on general principles of law and human rights. In contrast, military law is specific to TNI soldiers, with a focus on state security and military discipline, which can conflict with individual rights. The two legal instruments have differences in terms of principles, which of course can have legal implications. This difference also opens the door to opportunities for legal imbalances between military and criminal law in its enforcement. Human rights protection becomes fragile when the law raises question marks. This research focuses on the differences in the principles of criminal law and national military law against human rights, using a normative juridical method with a statutory approach and a conceptual approach to review regulations, norms, concepts, principles that will be associated with human rights.